New Proposals on Portuguese Vegetation (II) - Pinto-Gomes, Carlos; Paiva-Ferreira, Rodrigo; Meireles, Catarina (Lazaroa, 2011)
As a consequence of the geobotanical studies that have been developed in west and southern areas of the Iberian Peninsula, four new phytosociological associations are proposed, integrated in the perennial mesophytic grasslands of Stipo giganteae-Agrostietea castellanae (Serratulo flavescentis-Celticetum giganteae, Armerio macrophyllae-Celticetum giganteae, Centaureo rothmaleranae-Celticetum giganteae and Centaureo coutinhoi-Dactyletum lusitanici). For each proposed unit, besides its syntaxonomical fitting, we present its ecological diagnosis and the serial and catenal context, as well as its patrimonial value.